IJTIHAHAD, ITS SIGNIFICANCE, AND ITS IMPLEMENTATION IN MODERN AGE - Bashir Ahmed Rind; Ume Kulsoom Rind (دی اسکالر)
The Quran and Sunnah are two derivative sources of Islamic teachings.  The Quran and Sunnah explained away all those matters which do not change with passage of time and space such as beliefs, ritual worship and ethics.  However, there are certain matters pertaining to human life which do change with the passage of time and space such as political, social, cultural and economical issues. In fact the latter category of matters and issues could not have been explained away due to its ever-changing nature.  It is for this reason that the Quran and Sunnah laid down some fundamental principles through which these ever-changing matters and issues could be resolved. In order to find a resolution of these matters which are not explained away in the Quran and Sunnah, a sound knowledge of the Quran and Sunnah and hard mental work is required.  This type of hard work and strive is known as 'Ijtihad'. Ijtihad is one of the very significant religious, academic and mental tasks, which is beyond the capability of an ordinary man in the field.  Rather, this important task requires a specific capability and efficiency.  This article points out the meaning and significance of Ijtihad together with the specific capability of a person who conducts in Ijtihad and the matters in which an Ijtihad is allowed to be undertaken.